Transsexualism in Malaysia: is registration possible / Rozana Husin, Farah Wahida Md. Nor and Zarith Arbakin - Husin, Rozana; Md. Nor, Farah Wahida; Arbakin, Zarith (2006)
In this research we will discuss on the issue of transsexualism, which recently had made the head line in the news. It will focus on the legal recognition of the transsexuals especially after they had gone through the reassignment surgery. We are not looking for the recognition, but more to inquire about the situation regarding their status in the eye of Malaysian legal entity. It could be noted that in some country the transsexuals are recognize as what they claim as what they are. The sensitivity of this issue in respect of Malaysia which Islam is the official religion had made it difficult to be discuss openly. There are not many conferences nor were talks held to discuss this matter. The criminal aspect of transsexualism had been discussed. It is to see whether the surgery conducted is lawful or not. At the end of this research, we know that, Malaysia has no specific law governing transsexual community. Although Islam does recognize those categorize as Kunza or Hermaphrodites, but the law regarding them was no where to be found.